Index of orthodontic treatment need in children from the Niš Region - Janošević, Predrag; Stošić, Maja; Janošević, Mirjana; Radojičić, Julija; Filipović, Gordana; Čutović, Tatjana (Vojnosanitetski pregled, 2014)
Background/Aim. The Index of Orthodontic Treatment Need (IOTN) is a scoring system for malocclusion that consists of the two independent components: Denal Health Component (DHC) and Aesthetic Component (AC). IOTNs are usually used in the countries with dental healthcare financed by the government through the national healthcare system or healthcare insurance. The aim of the study was to determine IOTN in primary school children from the town of Niš and to asses percent of children with any kind of orthodontic treatment. Methods. The study involved 301 school children, 11–14 (12.4 ± 1.1) years old. The IOTN was used by the two examiners in order to evaluate the treatment need. Results. The results of the study showed that 111 (37%) out of 301 examined children had orthodonic treatment (33.33% boys and 66.67% girls) and they were excluded from the study. Out of final sample of 190 school children, considering DHC of the IOTN, 27.4% of the children showed great (grades 4–5), 41.0% moderate (grade 3) and 31.6% slight or no treatment need (grade 1–2). Considering IOTN AC, 15.3% of the children showed great (grade 8–10), 24.3 % moderate (grade 5–7) and 60.4% slight or no treatment need (grade 1–4). Conclusion. The need for orthodontic treatment in school children in the town of Niš, Serbia, is similar to the need in most European countries, despite the fact that the number of children orthodontically treated is much higher compared to most of European countries.